USE OF TRADITIONAL RECREATIONAL GAMES IN PHYSICAL EDUCATION CLASSES IN ELEMENTARY SCHOOL CLASSES IN THE EARLY YEARS - Castro de Matos, Cristiano (Revista Gênero e Interdisciplinaridade, 2023)
This work intends to approach aspects related to traditional recreational games, in the early years of elementary school. In the first part we will show how games can help in the physical, social, cognitive and learning development of students. Afterwards, we will deal with the case study methodology, conducting a survey with eight professors. We bring as a proposal how recreational games should be incorporated into physical education curricula.